A Sequential Mediating Role of GenAI Capability and Commit to Innovate in Employee Sensing Capability to Enhance Employee Innovative Work Behavior - Mahendra, Aji; Andriany, Lussia Mariesti; Pia G. Reyes, Alma (APMBA (Asia Pacific Management and Business Application), 2026)
A growing challenge for organizations in the digital era is how to effectively leverage employee capabilities and emerging technologies to sustain innovation performance. The purpose of this study is to examine how employee sensing capability (ESC) influences employees’ innovative work behavior (EWIB) in the workplace, using Gen AI usage capability (GAUIC) and commitment to innovation (CTI) as sequential mediating variables. This research uses a quantitative approach, and data were collected through an online questionnaire distributed to 200 workers in the architecture subsector in East Java Province. Data were analyzed using SmartPLS version 4.1.1.4, applying structural equation modeling—Partial Least Squares (SEM-PLS). The results indicate that all hypotheses are supported. ESC positively and significantly influences EWIB, both directly and indirectly through GAUIC and CTI. GenAI strengthens the effect of ESC on EWIB by facilitating innovation and ideation processes. In addition, commitment to innovation helps employees sustain innovative behavior when facing workplace challenges. Theoretically, this study extends the innovative work behavior model by introducing sensing capability and GenAI technology as key determinants in the digital context. Practically, the findings suggest that organizations should enhance sensing capability, GenAI literacy, and commitment to innovation through targeted training and innovation-based reward systems.